Short term outcome of treatment with percutaneous cross Kirschner wires in paediatric distal humeral metaphyseal diaphyseal junction fractures (Journal of Fatima Jinnah Medical University, 2023)
Background: Soft tissue sarcomas (STS) are malignant tumours arising from mesenchymal tissue, comprising
Keywords: Soft Tissue Sarcoma; Presentation; Resection; Histology